The Relationship of Myofascial Trigger Points (MTrPs) Pain to Headache: Type, Location, and Intensity of Headache - Novita Nurul K; Dessy Rakhmawati E.; Reza Maulana; Nasrul Musadir; Sofia Sofia (Rifa'Institute, 2022)
Headaches are one of the most common nervous system disorders with a major impact on public health. They can be caused by various etiologies, and some of them are symptoms of serious pathology. The location and intensity of the headache are related to the etiology of the headache. In some cases, headaches can be accompanied by pain due to myofascial trigger points (MTrPs), which are small hyper-irritating spots located centrally within bands that have been injured or overworked. The purpose of this study was to determine the relationship between Myofascial Trigger Points (MTrPs) Pain and the Type, Location, and Intensity of Headaches. This type of research is analytic observational with a cross-sectional design. Data were collected in October and December of 2014, and a sample of 50 people was drawn using a consecutive sampling technique.Data were gathered through neurologists' history-taking and physical examinations, as well as interviews using a numerical pain scale (NPS), and then analyzed using Fisher and Mann Whitney.The results showed that MTrPs were positive for M. sternocleidomastoid in 38 people, M. trapezius in 36 people, M. temporalis in 31 people, M. masseter superficialis in 20 people, M. suboccipital in 18 people, M. levator scapulae in 34 people, and M. obliquus superior in 20 people. The highest number of active MTrPs was 4 in 15 people, and referred pain from MTrPs was present in only 5 people. It can be concluded that there is no relationship between Myofascial Trigger Points (MTrPs) pain and the type of headache, but there is a relationship between Myofascial Trigger Points (MTrPs) pain and the location and intensity of the headache.